Strategi Penetapan Harga dan Tantangannya dalam Meningkatkan Margin Laba: Studi Alfamart - Gowasa, Winda; Yuliamir, Henry (Mahesa Research Center, 2025)
This article aims to analyze the pricing strategy implemented by Alfamart and its impact on sales levels and customer loyalty. The focus of the study is directed at how promotional pricing strategies, location-based price adjustments, and competitive pricing strategies affect the company's profitability amidst tight retail competition. A qualitative approach is used in this study by collecting data through in-depth interviews with marketing managers, direct observation at several Alfamart outlets, and analysis of financial documents and internal company reports. Data were analyzed using thematic analysis techniques to identify patterns from interviews and observations, and comparative analysis to evaluate the impact of strategies on increasing sales volume and customer loyalty. The results of the study indicate that the pricing strategy implemented contributed significantly to increasing sales in some cases, reaching an increase of up to 15% in certain promotional periods, and maintaining customer loyalty through bundling programs and exclusive discounts. However, this strategy also carries the risk of decreasing profit margins if promotional costs are not controlled efficiently. Internal factors such as operating costs, profit targets, and customer loyalty programs, as well as external factors such as market competition and fluctuations in raw material prices, have been shown to influence the company's pricing decisions. This study recommends that Alfamart optimize the use of data analytics to determine the effectiveness of promotional programs and implement AI-based dynamic pricing technology. These findings can also be a reference for other retail companies in designing adaptive and sustainable pricing strategies to maintain competitiveness and increase long-term profitability.